Understanding the motives and values of entrepreneurship with indigenous people: The case of indigenous-led social enterprises in Colombia - Calvo, Sara; Morales, Andrés (International Journal of Entrepreneurship and Innovation, 2023)
Few studies have been conducted on the value and motives of social entrepreneurship with indigenous people. The purpose of this paper is to examine the values and motives of social entrepreneurship and how it is experienced by indigenous groups in Colombia drawing on Structuration Theory theoretical framework. This work draws upon evidence from a multiple case study of five indigenous communities (Curripaco, Puinave, Yanacona, Misak and Wayuu) in three geographic regions. The analysis of the multiple case study using NVIVO.11, discovered internal and external motives and values. The internal drivers identified are Cosmovision, Ancestrality, Knowledge, Identity and Language and Community and Family Wellbeing. The external drivers are Land Rights and Territoriality, Armed Conflict and Violence, Socio Economic Needs: Poverty and lack of employment and Funding Opportunities. This paper brings into attention the importance of understanding the values and motives of social entrepreneurship within indigenous groups in Latin America.
Keywords: Colombia; entrepreneurship; indigenous people; Latin America; motives; social enterprises; values; Emerging; Scopus